The Relationship of Mother's Knowledge and Responsive Feeding Attitude with the Incidence of Stunting in Toddlers in the Central City Health Center Area, Gorontalo City - Sitti Azahra Suleman; Sri Andriani Ibrahim; Cindy Puspita Sari Haji Jafar (Universitas Muhammadiyah Palu, 2026)
This study aimed to analyze the relationship between maternal knowledge and responsive feeding attitudes with the incidence of stunting among toddlers in the working area of the Kota Tengah Health Center, Gorontalo City. This research employed a quantitative method with a cross-sectional design. The population consisted of all mothers who had toddlers with growth disorders/stunting, totaling 105 individuals, with a sample of 83 respondents selected using purposive sampling . Data were analyzed using univariate and bivariate analysis with the Chi-Square test. The results showed that the majority of mothers had a low level of knowledge (59%) and negative attitudes toward responsive feeding practices (63.9%). Furthermore, the prevalence of stunting among toddlers was relatively high at 61.4% . Statistical analysis indicated a significant relationship between maternal knowledge and stunting incidence (p = 0.000), as well as between maternal attitudes and stunting incidence (p = 0.011), where both p-values were less than 0.05. In conclusion, maternal knowledge and attitudes toward responsive feeding play an important role in the incidence of stunting among toddlers. Therefore, continuous health education is needed to improve mothers’ understanding and promote positive attitudes toward responsive feeding practices in order to reduce stunting rates.